Anti‐tumour effect of lapatinib in canine transitional cell carcinoma cell lines. (23rd September 2018) - Sakai, Kosei; Maeda, Shingo; Saeki, Kohei; Nakagawa, Takayuki; Murakami, Mami; Endo, Yoshifumi; Yonezawa, Tomohiro; Kadosawa, Tsuyoshi; Mori, Takashi; Nishimura, Ryohei; Matsuki, Naoaki
Abstract : Transitional cell carcinoma (TCC) accounts for >90% of canine malignant tumours occurring in urinary bladder, and the prognosis is poor. Our previous study, using RNA sequencing, showed that human epidermal growth factor 2 (HER2) was the most activated upstream regulator related to carcinogenesis in canine TCC. The aim of this study was to examine the anti‐tumour effect of lapatinib, a tyrosine kinase inhibitor of HER2, on canine TCC cell lines in vitro and in vivo. Five canine TCC cell lines (TCCUB, Love, Sora, LCTCC, and MCTCC) were used. Western blotting showed that HER2 protein expression was observed in all of the canine TCC cell lines. Lapatinib inhibited phosphorylation of HER2 and cell growth in a dose‐dependent manner. Cell cycle analyses using flow cytometry showed that lapatinib significantly increased the sub‐G1 and G0 /G1 phase fractions and significantly decreased the S and G2 /M phase fractions in the cell lines (Sora and TCCUB). For the in vivo experiments, the canine TCC cells (Sora) were subcutaneously injected into nude mice. Six days after inoculation, lapatinib (100 mg/kg) or vehicle was administered daily via intraperitoneal administration for 14 days. Tumour volume was significantly smaller in the lapatinib group compared with the vehicle control group. Histologically, lapatinib significantly increased necrotic areas in the tumour tissues. These findings suggest that lapatinib exerts anti‐tumour effects on canine TCC cells by inhibiting HER2 signalling and inducing cell cycle arrest.